2016
DOI: 10.3233/npm-16915120
|View full text |Cite
|
Sign up to set email alerts
|

Routine fecal occult blood testing does not predict necrotizing enterocolitis in very low birth weight neonates

Abstract: Positive FOB testing occurred in a majority of VLBW infants, with higher odds in the more preterm and IUGR. However, the sensitivity, specificity, and predictive value of routine FOB testing for identifying NEC were all very poor. Our data demonstrates that this test offers no advantages in the early diagnosis of NEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…This is supported by other studies that found that there is limited association between occult haematochezia and necrotising enterocolitis, and thus limited utility of routine faecal occult blood testing in infants. [10][11][12] Although there is no correlation between heme-positive stools and increased incidence of gastrointestinal emergencies, there were no gastrointestinal emergencies in the patients with hemenegative stools in our study.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…This is supported by other studies that found that there is limited association between occult haematochezia and necrotising enterocolitis, and thus limited utility of routine faecal occult blood testing in infants. [10][11][12] Although there is no correlation between heme-positive stools and increased incidence of gastrointestinal emergencies, there were no gastrointestinal emergencies in the patients with hemenegative stools in our study.…”
Section: Discussioncontrasting
confidence: 63%
“…9 In addition, studies have shown that the sensitivity, specificity, and positive predictive values of a positive faecal occult blood test among very low birth weight infants in the neonatal intensive-care unit were 0, 34.4, and 0%, respectively. 10 Due to the limited proven association between occult haematochezia and necrotising enterocolitis, some studies have found that routine faecal occult blood testing is not a useful diagnostic tool for neonatal patients. 11,12 As a result, some centres have discontinued routine testing.…”
mentioning
confidence: 99%
“…Numerous screening strategies have been attempted including routine fecal occult blood (FOB) testing and RGA monitoring. While routine FOB testing has been largely debunked and is falling out of favor (13,14), RGA persists despite limited supportive evidence. Early studies of RGA monitoring seemed to indicate that more frequent and larger gastric aspirate volumes could be predictive of NEC (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…Pickering A et al . 20 have reported that routine fecal occult blood testing does not predict necrotizing enterocolitis. Therefore, although we could not provide an early warning of severe disease though FOBT, and the early intervention for FOBT might not decrease NEC, sFA, structural bowel injuries, or any other complications, the significance of newborn FOBT positivity lies in that, medical staff would be alert to the related diseases including NEC, gastrointestinal malformations and suspected food allergy, with closer observation and follow-up.…”
Section: Discussionmentioning
confidence: 99%